Effect of Cone Diameter on Seed Yield, Moisture Content and Germination in Himalayan Blue Pine (Pinus wallichiana A.B. Jacks) - Singh, Virendra; Sah, V. K.; Bana, O. P. S. (Indian Forester, 1996)
The present study was aimed at, to find out the effect of different cone diameter classes (Small - < 3.0 cm; medium, 3.0 - 3.5 cm; and large - > 3.5 cm) on various parameters. The medium size cones exhibited higher germination followed by large size and small size cones in the laboratory as well as in the nursery. The large size cones were found superior in terms offresh weight of cones, quantity of seed extracted, fresh and dry weight of seeds and moisture content, respectively. However, the maximum per cent seed yield was obtained from the medium size cones. The number of cones required to get unit quantity of seed decreased as the diameter of cones increased. Therefore, it may be recommended that medium size cone be preferred for seed collection in order to obtain maximum germination in blue pine.